URGENSI PERLINDUNGAN HUKUM KONSUMEN E-COMMERCE DALAM PERDAGANGAN PRODUK KECANTIKAN DI KOTA PADANG - Desi Sommaliagustina; Helfira Citra; Sry Wahyuni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Electronic commerce is increasingly in demand by the public. One of them is trading beauty products electronically. The city of Padang is one of the cities that includes many electronic trading activities. E-commerce often encounters obstacles such as payment procedures, legal protection, electronic signatures, and dispute resolution mechanisms that may occur in the future. E- commerce must also comply with positive laws. Even though there are a number of barriers to e-commerce, this type of trading still has its fans. In addition, ignoring technological developments will have a negative impact in the future, so openness and being proactive and anticipatory are alternatives that can be chosen in dealing with the dynamics of technological developments including trade developments such as electronic commerce or what is commonly referred to as electronic commerce or e-commerce. This is because Indonesia has become part of the global e-commerce market. The focus of this research is: First, to determine legal protection for consumers in trading beauty products electronically in Padang City; Second, to find out the legal settlement in the event of a dispute by the parties in the e-commerce of beauty products in the city of Padang. The purpose of this research is to find out how legal protection is for consumers in trading beauty products electronically in Padang City and to find out how the legal settlement is in the event of a dispute by the parties in electronic trade in beauty products in Padang City.Keywords: Legal Protection, Consumers, E-Commerce, Beauty Products